Enhancing the ability of nurses and midwives to promote breastfeeding: a longitudinal study - Downie, Jill; Rakic, V.; Juliff, D. (Capers Bookstore, 2002)
Abstract: The research aimed to determine the effectiveness of the Lactation Adviser Program (LAP), six months following an educational intervention for nurses and midwives. Sixty one (61) participants were involved in the research, the second phase of a two phase, longitudinal study. The intervention involved twelve two hour sessions designed to increase nurses' and midwives' knowledge, attitudes and confidence toward lactation management in order to enable them to more appropriately promote breastfeeding among their clients. Using repeated measures MANOVA, the results showed the LAP intervention produced significantly higher knowledge scores in the experimental group compared to the control group over the time period. In addition, the interaction between knowledge and study group was significant demonstrating that the intervention had an effect on participant's knowledge six months following the program. Similarly, the results showed that the experimental group participants had significantly higher attitude scores than the control group across the time periods. Further analysis revealed that those who experienced the LAP developed more positive attitudes over the six month period, however, this was not maintained consistently at each time point. In the analysis of confidence scores across time, participants in the experimental group were no different to those in the control group. However, confidence was shown to be significantly higher in experimental group participants six months following the intervention. Overall, the results of the study were very positive in support of the Lactation Adviser Program as an effective initiative to increase knowledge and confidence and enhance positive attitudes of participants, in the long term, in regard to breastfeeding management. (author abstract)